Isolation and Biological Evaluation of Novel Tetracosahexaene Hexamethyl, an Acyclic Triterpenoids Derivatives and Antioxidant from Justicia adhatoda - Dhankhar, Sandeep; Dhankhar, Seema; Ruhil, Sonam; Balhara, Meenakshi; Malik, Vinay; K. Chhillar, Anil (Combinatorial Chemistry & High Throughput Screening, 2014)
Forty five extracts fraction of nine selected Indian medicinal plants, based on their use in traditional systems of medicine were analyzed for their antioxidant potential. All the extracts were investigated for phenol content value calculated in Gallic acid equivalents (% of GAE) and antioxidant potential. Moreover, total phenolic content (% dw equivalents to gallic acid) of all plant extracts were found in the range of 3.04 to 24.03, which correlated with antioxidant activity. The findings indicated a promising antioxidant activity of crude extracts fractions of three plants (Justicia adhatoda, Capparis aphylla and Aegle marmelos) and required the further exploration for their effective utilization. Results indicated that petroleum ether fraction of J. adhatoda out of three plants also possesses the admirable antioxidant abilities with high total phenolic content. Following, in vitro antioxidant activity-guided phytochemical separation procedures, twelve fractions of petroleum ether extract of J. adhatoda were isolated by silica gel column chromatography. One fraction (Rf value: 0.725) showed the noticeable antioxidant activity with ascorbic acid standard in hydroxyl radical scavenging assays. The molecular structures elucidations of purified antioxidant compound were carried out using spectroscopic studies (1H NMR, 13C NMR and MS). This compound was reported from this species for the first time. The results imply that the J. adhatoda might be a potential source of natural antioxidants and 2,6,10,14,18,22-Tetracosahexaene, 2,6,10,15,19,23-hexamethyl is an antioxidant ingredient in J. adhatoda.
Keywords: medicinal plants